2015
DOI: 10.1139/cgj-2014-0263
|View full text |Cite
|
Sign up to set email alerts
|

Field experimental cells to assess hydrogeological behaviour of store-and-release covers made with phosphate mine waste

Abstract: A field investigation was conducted to evaluate the effectiveness of store-and-release (SR) covers made with different phosphate mine wastes in reducing water infiltration (system inclination and surface runoff were neglected) and controlling acid rock drainage (ARD) generation. Four instrumented experimental cells were constructed with different SR layer configurations (two thicknesses and three materials) placed over a capillary break layer. To assess the hydrogeological behaviour of these cover systems, vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…This cover system allows the reduction of water infiltration and is considered to be one of the least expensive and most promising technologies, adapted to dry climate countries like Morocco ( Figure 1 ). The tested SDR cover system consisted in covering the AMD generating wastes with a 1 m layer of phosphate wastes that reduced water infiltration and, effectively decreasing AMD production [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This cover system allows the reduction of water infiltration and is considered to be one of the least expensive and most promising technologies, adapted to dry climate countries like Morocco ( Figure 1 ). The tested SDR cover system consisted in covering the AMD generating wastes with a 1 m layer of phosphate wastes that reduced water infiltration and, effectively decreasing AMD production [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such so-called store-and-release (SR, or alternate) covers have been shown to be quite efficient at reducing the quantity of water reaching the underlying waste, provided that the right materials are used to create the required capillary barrier effect (described below) and storage capacity. This type of cover has been constructed at the Barrick Goldstrike operation in Nevada, USA (Zhan et al 2000), and also applied within experimental cells at the Kettara mine, Morocco (Bossé et al 2015).…”
Section: Water Retention Coversmentioning
confidence: 99%
“…Passive Treatment. Store-and-release (SR) covers made with different phosphate mine wastes were studied for their effectiveness in reducing water infiltration and controlling AMD generation in a field investigation (Bosse et al, 2015). It was found that the studied scenarios limited deep water infiltration and the tested phosphate mine wastes had the appropriate hydrogeological properties In the USA, a dry flue gas desulfurization (FGD) product was investigated for abandoned coal mined land reclamation (Chen et al, 2015a).…”
Section: Treatment Optionsmentioning
confidence: 99%